2017
DOI: 10.1039/c6sm01752e
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of clusters of attractive dry and wet self-propelled spherical particle suspensions

Abstract: In order to asses the effect of hydrodynamics in the assembly of active attractive spheres, we simulate a semi-dilute suspension of attractive self-propelled spherical particles in a quasi two dimensional geometry comparing the case with and without hydrodynamics interactions. To start with, independently on the presence of hydrodynamics, we observe that depending on the ratio between attraction and propulsion, particles either coarsen or aggregate forming finite-size clusters. Focusing on the clustering regim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 63 publications
8
70
0
Order By: Relevance
“…In addition, recent simulations have shown that clusters are absent in 2D squirmer suspensions and in a 2D squirmer monolayer embedded in a 3D fluid [27,34]. While attractive interactions can lead to clustering [35][36][37], here we study swimmers with purely repulsive interactions to see role of hydrodynamics in active cluster formation.It is accepted from continuum arguments that the polar state is generically unstable for wet active systems [1][2][3], however recent simulations of wet active particles have raised the interesting possibility of other continuum limits in these systems. A polar state has been observed for neutral squirmers with no force dipole with 3D hydrodynamics, but 2D motion [19] and in 3D [38][39][40].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent simulations have shown that clusters are absent in 2D squirmer suspensions and in a 2D squirmer monolayer embedded in a 3D fluid [27,34]. While attractive interactions can lead to clustering [35][36][37], here we study swimmers with purely repulsive interactions to see role of hydrodynamics in active cluster formation.It is accepted from continuum arguments that the polar state is generically unstable for wet active systems [1][2][3], however recent simulations of wet active particles have raised the interesting possibility of other continuum limits in these systems. A polar state has been observed for neutral squirmers with no force dipole with 3D hydrodynamics, but 2D motion [19] and in 3D [38][39][40].…”
mentioning
confidence: 99%
“…In addition, recent simulations have shown that clusters are absent in 2D squirmer suspensions and in a 2D squirmer monolayer embedded in a 3D fluid [27,34]. While attractive interactions can lead to clustering [35][36][37], here we study swimmers with purely repulsive interactions to see role of hydrodynamics in active cluster formation.…”
mentioning
confidence: 99%
“…Our findings should complement more detailed work that could connect our activity channels to microscopic interactions [6][7][8][9][10]. They may also be be relevant to continuum models of multiple species (some non-conserved [30]) that were used recently to study microphase separations used by cells to create cytoplasmic and nucleoplasmic organization [31,32].…”
mentioning
confidence: 53%
“…A generic understanding of such nonequilibrium microphase separations can be sought at the level of continuum equations for a diffusive scalar concentration field, coupled to incompressible fluid flow. Such an approach is complementary to more detailed mechanistic modelling, in which particle motion and/or chemical fields are modelled explicitly [6][7][8][9][10]. By sacrificing detail, the resulting 'active field theory' allows maximal transfer of ideas and methods from equilibrium statistical mechanics.…”
mentioning
confidence: 99%
“…As in Ref. [26], we quantify the competition between attractive and self-propelling forces via the dimensionless parameter…”
Section: Simulation Detailsmentioning
confidence: 99%